Vitamin D2: New Perspectives in Drawing. - Garrett, Craig; Aguirre, Peio; Budak, Adam; Cooke, Lynne; Dziewior, Yilmaz; Ferguson, Alex; Golden, Thelma; Joo, Eungie; Kapur, Geeta; Lind, Maria; Njami, Simon; Scott, Kitty; et al. (London : Phaidon, 2013)
Akunyili, Njideka ; Aran, Uri ; Ashoona, Shuvinai ; Boghiguian, Anna ; Bronstein, Pablo ; Chan, Paul ; Gastaldon, Vidya ; Huddleston, Donna ; Jamie, cameron ; Jurczak, Dorota ; Kopelman, Irene ; Kunath, Friedrich ; Mir, Aleksandra ; Pica, Amalia ; Plender, olivia ; Qureshi, Imran ; Reid Kelley, Mary ;Sietsema, Paul ; Sokolow, Deb ; Treister, Suzanne ; trouvé, tatiana ; Villar Rojas ; Van de Velde , Rinus
boek